Influence of plasma nucleus form on radiation orientation in high-current pulse plasma diode - Tseluyko, A.F.; Lazurik, V.T.; Ryabchikov, D.L.; Hassanein, A.; Maslov, V.I.; Borgun, I.V.; Sereda, I.N. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The factors accompanied the generation directed super-radiation in high-current pulse discharge in tin vapor are investigated. Basing on measurements of space distribution of radiation intensity and fixing of discharge evolution phases images it was shown that generation of directed super-radiation occurs in the moment of plasma jet gushes from dense plasma formations situated close to the anode, and the orientation of super-radiation is the same as the plasma jet one. It was drown a conclusion about the presence of radiation-stimulated radiation effect in multiply ionized plasma.